Neuroprotective effects of germinated brown rice against hydrogen peroxide induced cell death in human SH-SY5Y cells - Ismail, Norsharina; Ismail, Maznah; Fathy, Siti Farhana; Musa, Siti Nor Asma; Imam, Mustapha Umar; Foo, Jhi Biau; Iqbal, Shahid (MDPI, 2012)
The neuroprotective and antioxidative effects of germinated brown rice (GBR), brown rice (BR) and commercially available γ-aminobutyric acid (GABA) against cell death induced by hydrogen peroxide (H2O2) in human neuroblastoma SH-SY5Y cells have been investigated. Results show that GBR suppressed H2O2-mediated cytotoxicity and induced G0/G1 phase cell cycle arrest in SH-SY5Y cells. Moreover, GBR reduced mitochondrial membrane potential (MMP) and prevented phosphatidylserine (PS) translocation in SH-SY5Y cells, key features of apoptosis, and subsequent cell death. GBR exhibited better neuroprotective and antioxidative activities as compared to BR and GABA. These results indicate that GBR possesses high antioxidative activities and suppressed cell death in SH-SY5Y cells by blocking the cell cycle re-entry and apoptotic mechanisms. Therefore, GBR could be developed as a value added functional food to prevent neurodegenerative diseases caused by oxidative stress and apoptosis.